Indoor Localization-based Energy Management for Smart Home - Shan, Gaoyang; Lee, Hojin; Roh, Byeong Hee (Asia-Pacific Power and Energy Engineering Conference, APPEEC, 2022)
With the development of the Internet of Things (IoT) industry, many services and applications have been developed, such as indoor localization, proximity detection, smart home, and so on. However, many services are severely limited due to energy constraints. Many researchers have proposed solutions to reduce energy consumption in these applications and improve energy utilization. For instance, Bluetooth low energy (BLE)-based data transmission scheme and sensor-based energy management scheme. In this paper, we combine BLE and sensors to propose an indoor localization-based energy management system for smart homes, which can effectively solve the energy waste caused by users forgetting to turn off the device's power. The analysis results show that the proposed scheme can save energy effectively.
Keywords: Bluetooth low energy; Energy constraint; Energy-based; Indoor localization; Internet of things industries; Lower energies; Proximity detection; Reduce energy consumption; Services and applications; Smart homes; Bluetooth low energy; Energy management; Indoor localization; Smart home